Some Important Features of the Socialistic Forestry of German Democratic Republic - Verma, V. P. S. (Indian Forester, 1971)
Important features of the forestry in GDR like production and important of wood, position of growing stock and increment, forest area and spp. Etc., are dealt. The administrative setup of the department in a socialist society is discussed. The developments in the silviculture and utilisation of forests have been described. Other features like ameliorative measures for improvement of soils are also touched upon.